Mitigating the adverse impact of drought stress on germination and related traits of Chickpea through seed priming with iron nanoparticles and bulk form - Nasrin Teimoori; Mohsen Saeidi; Mahmood Khoramivafa; Shahab Khoshkhoi (علوم و فناوری بذر ایران, 2025)
The utilization of nanoparticles for seed priming may enhance the germination and seedling growth compared to bulk forms. Therefore, this research aims to investigate the effect of seed priming (with bulk iron oxide, nanoparticles of 1-100 nm and 40-60 nm in concentrations of zero, 2, 4, and 8 g l-1, water, and no priming) at different levels of drought stress (including no stress, -2, -4 and -8 bar) using polyethylene glycol 6000 on the characteristics of germination and growth of Adel chickpea cultivar. This research was performed as a factorial experiment based on a completely randomized design in three replications at Razi University. The results showed that germination ceased completely under drought stress of -8 bar. Drought stress at -4 bar after -8 bar resulted in a significant decrease in the percentage, speed, and vigor of germination by 96, 93, and 40%, respectively, and 130% increase in root length/shoot length ratio compared to the non-drought stress treatment. Seed priming treatments had the most positive and significant effect on the speed and vigor of germination in non-drought stress treatment and on the germination percentage in drought stress treatment. The seed priming with iron 8 g l-1 and 40-60 nm produced the highest length and weight vigor of germination. It appears that the priming treatments have resulted in better vigor and rate of germination in non-drought stress condition while germination percentage in drought stress. The seed priming treatment using iron 40-60 nm is the most effective compared to other priming treatments.